An Effective and Practical Fluid Restriction Protocol to Decrease the Risk of Hyponatremia and Readmissions After Transsphenoidal Surgery. Issue 4 (28th January 2020) - Winograd, Dina; Staggers, Kristen A; Sebastian, Sherly; Takashima, Masayoshi; Yoshor, Daniel; Samson, Susan L
Abstract: BACKGROUND: Delayed hyponatremia is a common complication following transsphenoidal surgery (TSS) of pituitary lesions, which leads to significant patient morbidity, as well as increased hospital costs associated with readmission. OBJECTIVE: To report the effects of fluid restriction, during a postoperative period of 4 d, to decrease rates and readmissions for hyponatremia in a cohort of patients undergoing TSS. METHODS: Because of our observed postoperative rates of hyponatremia, we implemented 1000-mL fluid restriction limited to postoperative days (POD) 4 to 8 in consecutive patients undergoing surgery at our center between March 2018 and January 2019. Patients were monitored for the development of hyponatremia and readmissions. We compared outcomes with those of patients who had undergone TSS prior to fluid restriction. RESULTS: Data from 57 patients who underwent TSS following implementation of fluid restriction were compared to prior patients who underwent TSS without restriction. The rate of hyponatremia in patients (n = 57) prior to fluid restriction was 12.3%. Following implementation of fluid restriction, we had zero cases of hyponatremia or readmissions. We found body mass index to be inversely related to the risk of hyponatremia and readmissions. Furthermore, male gender, follicle stimulating hormone and/or luteinizing hormone staining on pathology, and administration of preoperative and intraoperative glucocorticoids were associated with decreased risk of hyponatremia readmissions. CONCLUSION: The implementation of 1000-mL fluid restriction between POD 4 and 8 is a highly successful and simple approach to decrease the risk of delayed hyponatremia after TSS.